Bone repair of critical-sized defects in Wistar rats treated with autogenic, allogenic or xenogenic bone grafts alone or in combination with natural latex fraction F1 - Santos Kotake, Bruna Gabriela (2018)
Bone grafts are used in the medical-surgical field for anatomical and functional reconstruction of lost bone areas, aiding the bone repair process by osteogenesis, osteinduction and osteoconduction. New materials such as F1 (fraction 1) protein extracted from the rubber tree Hevea brasiliensis have been investigated and currently present important properties for tissue repair, and are associated with neoangiogenesis, promoting cell adhesion and extracellular matrix formation. The main objective of this study was to investigate the association of F1 protein to different bone grafts in the repair of critical bone defects in the calvaria of Wistar rats. A total of 112 Wistar rats were divided as follows: autograft (AuG), allograft (AlG), xenograft (XeG), autograft/F1 (AuG-F1), allograft/F1 (AlG-F1), xenograft/F1 (XeG-F1), F1(F1), control (CTL), with a waiting period of 4 and 6 weeks (w). The stereological AuG, AlG, AuG-F1 and AlG-F1 results had greater bone neoformation (p < 0.05). For immunohistochemistry, the angiogenic and osteogenic factors were higher for AuG-F1 and AlG-F1. TRAP positive cells were higher in XeG-F1 and AlG (37 +/- 9.53, 13.3 +/- 4.16) (4 w) and XeG, AlG-F1 and XeG-F1 (20.33 +/- 7.37; 15.25 +/- 6.02, 19.33 +/- 3.21) (6 w). For zymography, F1 showed increased gelatinolytic activity of MMP-2 and -9. It was concluded that the bone graft associated or not with F1 increases the angiogenic and osteogenic, biochemical and stereological factors.